2006
DOI: 10.1029/2005gc001120
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and compositional structure of the subcontinental lithospheric mantle: Derivation from shear wave seismic tomography

Abstract: [1] Seismic tomography can provide unique information on the structure of the subcontinental lithospheric mantle (SCLM), but seismic velocity reflects both temperature and composition. We present a methodology for evaluating and isolating the relative contributions of these effects, which produces maps of regional geotherm and broad compositional constraints on the SCLM from the inversion of shear wave (Vs) seismic tomography. This approach uses model geotherms quantized in steps of 2.5 mW/m 2 and three mantle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 36 publications
7
47
0
3
Order By: Relevance
“…2B and 3) similar to those of Ritsema and van Heijst (2000), Shapiro and Ritzwoller (2002), Deen et al (2006), Pasyanos and Nyblade (2007), and Begg et al (2009) models. However, the faster S-wave velocity anomalies observed at 0-100 km depth under the Saharan Metacraton decrease sharply to nearly zero at 100-175 km depth (Fig.…”
Section: -175 Km Depthsupporting
confidence: 70%
See 3 more Smart Citations
“…2B and 3) similar to those of Ritsema and van Heijst (2000), Shapiro and Ritzwoller (2002), Deen et al (2006), Pasyanos and Nyblade (2007), and Begg et al (2009) models. However, the faster S-wave velocity anomalies observed at 0-100 km depth under the Saharan Metacraton decrease sharply to nearly zero at 100-175 km depth (Fig.…”
Section: -175 Km Depthsupporting
confidence: 70%
“…The Ritsema and van Heijst (2000) model shows that the faster S-wave velocity under Egypt persists down to a depth of 150 km, but this disappears at 200 km depth where much of the Saharan Metacraton is shown as been underlain by velocities equal to PREM. Additionally, the Saharan Metacraton was imaged as underlain by a slightly higher velocity relative to PREM at 100-175 km in Deen et al (2006) using S-wave velocity model derived from Grand (2002). The velocity values were not specified in the presentation of Deen et al (2006), but it can be concluded that these are not as high as those under other African cratons.…”
Section: -175 Km Depthmentioning
confidence: 98%
See 2 more Smart Citations
“…In Africa, which in many reconstructions is put as the heart of Greater Gondwana [Irving and Irving, 1982;Smith and Hallam, 1970], surface geological mapping, geochemical and geochronological studies together with low resolution seismic tomography [Abdelsalam et al, 2011;Begg et al, 2009;Deen et al, 2006;Lebedev et al, 2009;Pasyanos, 2010;Pasyanos and Nyblade, 2007;Ritsema and van Heijst, 2000;Shapiro and Ritzwoller, 2002] have resulted in establishing the extent of major cratons and orogenic belts of Greater Gondwana (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%